Regulatory T-cell depletion in the setting of autologous stem cell transplantation for multiple myeloma: pilot study. Issue 1 (15th January 2020) - Derman, Benjamin A; Zha, Yuanyuan; Zimmerman, Todd M; Malloy, Rebecca; Jakubowiak, Andrzej; Bishop, Michael R; Kline, Justin
Abstract : Background: Progression after high-dose melphalan with autologous stem cell transplantation (ASCT) in multiple myeloma (MM) may be due in part to immune dysfunction. Regulatory T (Treg) cells reconstitute rapidly after ASCT and inhibit immune responses against myeloma cells. Methods: We performed a randomized study to evaluate two methods of Treg depletion in patients with MM undergoing ASCT. No Treg depletion was performed in the control ASCT arm. An anti-CD25 monoclonal antibody (basiliximab 20 mg IV) was administered on day +1 post-ASCT in the in vivo Treg depletion (IVTRD) arm. Tregs were depleted from autologous stem cell (ASC) grafts with anti-CD25 microbeads and the CliniMACS device in the ex vivo Treg depletion (EVTRD) arm. Results: Fifteen patients were enrolled, five in each arm. The conditioning regimen was melphalan 200 mg/m 2 . Primary objectives included assessments of efficiency of IVTRD/EVTRD, kinetics of Treg depletion and recovery following ASCT, and safety. EVTRD removed 90% of CD4 + CD25 + cells from ASC grafts. IVTRD and EVTRD led to reductions in Treg frequency between days +7 and +90 post-transplant compared with the control (p=0.007 and p<0.001, respectively). Conclusions: IVTRD and EVTRD are feasible and significantly reduce and delay Treg recovery post-ASCT for MM, and serve as a platform for using post-transplant immunotherapies to improve post-ASCT outcomes. Trial registration number: NCT01526096 .